2016
DOI: 10.1007/s11682-016-9658-7
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of increased risk-taking propensity in sleep-deprived people along with a changing risk level

Abstract: Risky decision-making under a changing risk level is a complex process involving contextual information. The neural mechanism underlying how sleep deprivation (SD) influences risky decision-making behaviors with a changing risk level has yet to be elucidated. In this study, we used the Balloon Analogue Risk Task (BART) during functional magnetic resonance imaging to investigate the neural correlates of SD-induced changes on decision-making behaviors at different risk levels. Thirty-seven healthy male adults we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…For each bootstrapping run, a common dictionary containing k atoms with the corresponding spatial maps was learned to represent the concatenated fMRI signals from the selected samples. In addition, the eta 2 was applied to estimate the similarity of two spatial maps [Lei et al, ]. eta2=1SSWithinSSTotal=1i=1v[false(aimifalse)2+false(bimifalse)2]i=1v[false(aiM¯false)2+false(biM¯false)2] where a i and b i are the values in position i of matrix a and matrix b , m i is the mean of a i and b i , and M¯ is the grand mean value across all positions in the two matrices.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For each bootstrapping run, a common dictionary containing k atoms with the corresponding spatial maps was learned to represent the concatenated fMRI signals from the selected samples. In addition, the eta 2 was applied to estimate the similarity of two spatial maps [Lei et al, ]. eta2=1SSWithinSSTotal=1i=1v[false(aimifalse)2+false(bimifalse)2]i=1v[false(aiM¯false)2+false(biM¯false)2] where a i and b i are the values in position i of matrix a and matrix b , m i is the mean of a i and b i , and M¯ is the grand mean value across all positions in the two matrices.…”
Section: Methodsmentioning
confidence: 99%
“…This study recruited 37 right‐handed healthy adult males (mean ± STD age, 23.1 ± 1.9 years). The data were previously used to probe the neural correlates of increased risk‐taking propensity in sleep‐deprived people [Lei et al, ]. All participants had habitually good sleeping habits (asleep no later than 12:00 pm and awake at no later than 8:00 am) and slept at least 6.5 h (average: 7.5 ± 0.7 h) each night for the last month.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of sleep may have a negative impact on risky decision-making. However, results on how SD affects risky decision-making remain inconsistent [ 17 , 18 , 19 ]. Some studies have shown that after SD, participants are more risk-seeking, while other studies have reached the opposite conclusion [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The larger number of pumps participants made for each balloon, the greater risk level participants are willing to take. Due to its high ecological validity, the BART was widely used to explore the real‐life risky behavior (Aklin et al, 2005 ; Lejuez et al, 2002 ; Lejuez, Aklin, Jones, et al, 2003 ; Lejuez, Aklin, Zvolensky, et al, 2003 ; Lejuez et al, 2007 ; MacPherson et al, 2010 ), personalities (Mishra & Novakowski, 2016 ; Parkinson et al, 2012 ), psychophysiological processes and disorders (Lei et al, 2017 ). A recent review found that, compared with the Iowa gambling task (IGT), delay discounting task, and other decision tasks, the BART is the most sensitive task to detect alcohol users' risk‐taking behavior (Harmon et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%